Recurrent acute pancreatitis caused by pancreatic biliary maljunction due to long common channel - Farias, Galileu F. A. (2017)
The pancreatic biliary maljunction is a rare anomaly that affects mainly females, defined as an anatomical maljunction of the pancreatic duct and the biliary duct confluence, and may be a rare cause of recurrent acute pancreatitis. In order to early diagnosis and prompt treatment, ERCP has an important role in it.